2023
DOI: 10.1111/ijfs.16369
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin/chitosan nanofibres containing β‐cyclodextrin complex and corn poppy (Papaver rhoeasL.) for intelligent packaging

Abstract: This study aimed to produce an intelligent gelatin film containing chitosan nanofibre (CNF) and β-cyclodextrin/corn poppy complex (β-CD/CP) and monitor shrimp spoilage. The crystalline properties, surface morphology and chemical structure of the films were characterised. The results showed that the addition of CNF caused the appearance of a new peak at 2θ = 12.16°and improved the crystalline properties of the film. According to Fourier Transform Infrared (FT-IR) results, new interactions were formed between CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Anthocyanin provides red, blue, and purple colors to plants in a water-soluble pigment [69]. The red color of poppy is related to the inclusion of various anthocyanins such as coumarin, rutin, cyanidol, malvidin, luteolinidin, and vitexin [70]. Velickovic et al (2019) reported that the most represented anthocyanins in the extracts of Papaver rhoeas L. are cyanidin-3-O-rutinoside, cyanidin-3-O-glucoside, delphinidin-3-p-coumaroylglucoside, delphinidin-3-O-glucoside, peonidin-3-O-glucoside, petunidin-3-acetylglucoside, and petunidin-3-O-glucoside [71].…”
Section: Total Anthocyanin Contentmentioning
confidence: 99%
“…Anthocyanin provides red, blue, and purple colors to plants in a water-soluble pigment [69]. The red color of poppy is related to the inclusion of various anthocyanins such as coumarin, rutin, cyanidol, malvidin, luteolinidin, and vitexin [70]. Velickovic et al (2019) reported that the most represented anthocyanins in the extracts of Papaver rhoeas L. are cyanidin-3-O-rutinoside, cyanidin-3-O-glucoside, delphinidin-3-p-coumaroylglucoside, delphinidin-3-O-glucoside, peonidin-3-O-glucoside, petunidin-3-acetylglucoside, and petunidin-3-O-glucoside [71].…”
Section: Total Anthocyanin Contentmentioning
confidence: 99%
“…The results showed that, during storage, the film changed from coral to gold due to changes in pH (8.3 to 10.5) and the release of ammonium vapors due to protein decomposition. Demonstrating that this intelligent film could effectively be applied to marine products to monitor their shelf life [138].…”
Section: Ph Indicatorsmentioning
confidence: 99%
“…The results showed that, during storage, the film changed from coral to gold due to changes in pH (8.3 to 10.5) and the release of ammonium vapors due to protein decomposition. Demonstrating that this intelligent film could effectively be applied to marine products to monitor their shelf life [144].…”
Section: Ph Indicatorsmentioning
confidence: 99%